2019
DOI: 10.1186/s13018-019-1320-9
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid α-defensin in the diagnosis of periprosthetic joint infection: the lateral flow test is an effective intraoperative detection method

Abstract: Background Synovial fluid α-defensin is a valuable biomarker for periprosthetic joint infection (PJI). Its diagnostic value for PJI has been widely evaluated recently, but results are inconsistent, especially for different test methods. The objective of this study was to evaluate the diagnostic value of laboratory-based immunoassay and lateral flow testing for the detection of α-defensin against hip and knee PJI. Methods We systematically searched MEDLINE and EMBASE for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 64 publications
2
12
0
1
Order By: Relevance
“…The diagnostic reliability and accuracy of α‐defensin in PJI has been widely evaluated during the past few years 12,24,27,36,39,42 , and some studies have confirmed that α‐defensin is highly accurate for diagnosing PJI 27,36,39,42,44 . While some indicate that the α‐defensin lateral flow test is less sensitive and may be used as a confirmatory test for PJI 23,39 . This systematic review and meta‐analysis of 17 studies indicated that the α‐defensin lateral flow test had a pooled sensitivity, specificity, and AUC of 0.83 (95% CI 0.77, 0.88), 0.95 (95% CI 0.93, 0.97), and 0.97 (95% CI 0.95, 0.98), respectively.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The diagnostic reliability and accuracy of α‐defensin in PJI has been widely evaluated during the past few years 12,24,27,36,39,42 , and some studies have confirmed that α‐defensin is highly accurate for diagnosing PJI 27,36,39,42,44 . While some indicate that the α‐defensin lateral flow test is less sensitive and may be used as a confirmatory test for PJI 23,39 . This systematic review and meta‐analysis of 17 studies indicated that the α‐defensin lateral flow test had a pooled sensitivity, specificity, and AUC of 0.83 (95% CI 0.77, 0.88), 0.95 (95% CI 0.93, 0.97), and 0.97 (95% CI 0.95, 0.98), respectively.…”
Section: Discussionmentioning
confidence: 86%
“…It induces rapid death of the microorganisms by promoting depolarization of the cell membrane via interacting with or binding to the negatively charged membranes 16,21,22 . Recent evidence shows that Alpha‐defensin might be an ideal biomarker for PJI 14,23 . Ahmad et al 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Produced primarily by PMN, α‐defensins are a set of related low molecular weight polypeptides (called antimicrobial peptides) that have antibacterial activity 14 . When used for the diagnosis of PJI in SF, it achieved sensitivity and specificity of over 90% in the hands of multiple investigators 14,69–74 . In addition, a recently introduced lateral flow immunoassay kit, Synovasure, is now recommended for rapid analysis (~20 minutes) in the surgical suite, though it was found to be slightly less sensitive 15,16,74 .…”
Section: New Advancements In Diagnosis Of Pjimentioning
confidence: 99%